(untitled) (Journal of Economic Additions, 2025)
This paper examines the role of local taxation, particularly the professional activity tax introduced in 1996, in financing municipal budgets and strengthening financial autonomy from central authority. The study reviews fiscal reforms in Algeria and analyzes revenues from this tax through a case study of Ghardaïa municipalities (2017–2020). Findings confirm that local taxation remains a vital source of revenue, enabling municipalities to achieve financial independence and support local development. JEL Classification Codes: H71, H79